Using minimum effort duration can compromise the analysis of acceleration and deceleration demands in football - Silva, H.; Nakamura, F. Y.; Ribeiro, J.; Asian-Clemente, J.; Roriz, P.; Marcelino, R. (International Journal of Performance Analysis in Sport, 2023)
The aim of this study was to characterise football players` acceleration and deceleration demands regarding duration, initial velocity, and effort magnitude without a minimum effort duration. Forty-two male professional players were monitored daily during four training weeks, using a global position system. Players were divided according to their playing positions as central defenders, fullbacks, central midfielders, wide midfielders, and forwards. Acceleration and deceleration efforts were analysed from the start of the change in velocity until it stopped increasing (acceleration) or decreasing (deceleration). Descriptive statistics were performed for occurrences, initial velocities, and average and peak magnitudes. Comparisons between playing positions were conducted with one-way analysis of variance (ANOVA). The frequency of accelerations and decelerations decreased as the duration increased. The initial deceleration velocity increased with duration, but no changes were seen in the acceleration initial velocity. The average effort`s magnitude increased with duration, while the peak magnitudes decreased, showing acceleration and deceleration peaks between 0.5-1.3 and 0.1-0.3 s, respectively. Differences between playing positions occurred between 0.7 and 2.5 s. In conclusion, the measurement of accelerations and decelerations should avoid the use of minimum effort duration since it can modify the real training load of football players.